Correlation between Kupffer Cell Infiltration and Liver Parenchymal Cell Damages in Immunosuppressed Drugs-Induced Rats (Majalah Kedokteran Bandung, 2024)
The liver is the largest organ in the body, composed of both parenchymal and non-parenchymal cells. Chemical substances and various drugs can induce liver injury and involve Kupffer cells which are non-parenchymal cells that release biologically active substances, promoting pathological processes. This study aimed to evaluate the correlation between the number of Kupffer cells and liver parenchymal cell damages in immunosuppressed, drug-induced rats. The study was conducted from July to December 2019 at the Oral Biology Laboratory of the Faculty of Dentistry and the Biochemical Laboratory of the Faculty of Medicine at Universitas Hang Tuah Surabaya. Twelve healthy male Wistar rats were divided into two groups: Healthy (H) and Immunosuppressed Drug-Induced (ID) groups. Immunosuppression was induced using dexamethasone (0.5 mg/day/rat), administered orally for 14 days, combined with tetracycline (1%/day/rat). Liver samples from all rats were examined for Kupffer cell count and parenchymal cell damages were assessed using a light microscope with 400x magnification. Results revealed a significant difference in the number of Kupffer cells and liver parenchymal cell damages between the H and ID groups (p
Keywords: Immunosuppressed drugs; Kupffer cell; liver parenchymal cell